Workplace Bullying and Performance of Employees: Manufacturing Firms Perspective in Anambra State - Patrick, Okeke Anene; Chike , Nwosu; Phina, Onyekwelu Njideka (Goodwood Publishing, 2022)
Purpose: This study determined workplace bullying and how it affects employees' performance, while it specifically examined workplace aggression and how it relates to the occupational stress of workers in the selected manufacturing firms in Anambra State. Research Methodology: The study made use of a survey research design. The population consisted of 167 staff of 10 selected manufacturing and made use of the census method in sampling. The data collection instrument was a Likert-structured questionnaire which was subjected to both validity and reliability tests. Data analysis was done using simple regression and the hypothesis was tested at a 5% level of significance. Result: The finding revealed that a positive relationship exists between workplace aggression and occupational stress and that a 90% change in occupational stress is a result of changes in workplace aggression (R = .904; R2 = 898; F statistics = 7097.588; p-value < .05). Limitation: The study made use of just 10 manufacturing firms which might reduce the inferrability of the work. Contribution: The study provided empirical evidence as to the relationship between workplace aggression and occupational stress in manufacturing firms in Anambra State which appear not to have been done before. Novelty: The study made use of a self-structured questionnaire that took into consideration the operational environment of the firms and the characteristics of the employees and work relationships.